HUBUNGAN ANTARA STUDENT ENGAGEMENT DAN DETERMINASI DIRI DENGAN SCHOOL WELL-BEING PADA SISWA KELAS VII DAN KELAS VIII DI SMP NEGERI 2 KOTA SEMARANG - Nisa, Zahrotun; Indrajati Kunwijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between student engagement and self-determination with school well-being in junior high school students. The approach used in this study is quantitative with correlational methods. The research subjects were 201 junior high school students selected using a multistage sampling technique. Data collection was carried out using the school well-being scale, student engagement scale, and self-determination scale. Data were analyzed using multiple linear regression analysis with the help of the IBM SPSS 26 program. The results showed that there was a significant relationship between student engagement and self-determination with school well-being in junior high school students with an F count value of 116.560 and a significance of 0.000 (p < 0.05). The Adjusted (R) value of 0.536 indicates that student engagement and self-determination contributed 53.6% to school well-being, while the rest was influenced by other factors outside the study. The results of the regression analysis showed that student engagement and self-determination had a positive influence on school well-being. In addition, self-determination was the variable that provided a more dominant contribution than student engagement.  Based on the research results, it can be concluded that the higher the student engagement and self-determination, the higher the level of school well-being of junior high school students. Therefore, efforts are needed from schools to increase student engagement in learning and develop self-determination to improve student well-being at school.